Social development and informal markets: lessons from Thohoyandou market, South Africa. Issue 1 (2nd January 2017) - Vermaak, Jaco
ABSTRACT: This article explores informal markets as spaces of socialisation. Informal markets are important given the increase in migrants seeking a better life in cities and the need to formulate appropriate development policies. The methodology used involved a literature study that focused on social adaptation, and fieldwork done at an informal market in South Africa. The results show that informal traders are able to adapt to difficult circumstances by using informal networks, and also that they can remain victims trapped in poverty if they accept their powerless situations.